Exosomal Long Non-coding RNAs: Emerging Players in the Tumor Microenvironment - Anup S. Pathania; Kishore B. Challagundla (Elsevier, 2021)
Recent advances in exosome biology have uncovered a significant role of exosomes in cancer and make them a determining factor in intercellular communication. Exosomes are types of extracellular vesicles that are involved in the communication between cells by exchanging various signaling molecules between the surrounding cells. Among various signaling molecules, long non-coding RNAs (lncRNAs), a type of non-coding RNA having a size of more than 200 nt in length and lacking protein-coding potential, have emerged as crucial regulators of intercellular communication. Tumor-derived exosomes containing various lncRNAs, known as exosomal lncRNAs, reprogram the microenvironment by regulating numerous cellular functions, including the regulation of gene transcription that favors cancer growth and progression, thus significantly determining the biological effects of exosomes. In addition, deregulated expression of lncRNAs is found in various human cancers and serves as a diagnostic biomarker to predict cancer type. The present review discusses the role of exosomal lncRNAs in the crosstalk between tumor cells and the surrounding cells of the microenvironment. Furthermore, we also discuss the involvement of exosomal lncRNAs within the tumor microenvironment in favoring tumor growth, metabolic reprogramming of tumor cells, and tumor-supportive autophagy. Therefore, lncRNAs can be used as a therapeutic target in the treatment of various human cancers.